Class pi glutathione S-transferase: unfolding and conformational stability in the absence and presence of G-site ligands - Erhardt, Julija (My University, 1996)
The glutathione S-transferases (GST) are a supergene family of h0111o-or heterodimeric Phase II detoxification enzymes which catalyse the S-conjugation between glutathione and an electrophilic substrate. The active site can be divided into two adjacent functional regions; a highly specific Gssite for binding the physiological substrate glutathione and a nonspecific If-site for binding nonpolar electrophilic substrates. Unfolding of porcine class Pi isoenzyme (pGSTPl~l) was monitored under equilibrium conditions using different physicochemical parameters. The coincidence of unfolding curves obtained with functional and structural probes, the absence of thermodynamically stable intermediates such as a folded monomer, and the dependence of pGSTPl··l stability upon protein concentration, indicate a cooperative and concerted two-state unfolding transition between native dimeric pGSTPl-l and unfolded monomeric enzyme. Equilibrium and kinetic unfolding experiments employing tryptophan fluorescence and enzyme activity measurements were preformed to study the effect of ligand binding to the G-site on the unfolding and stability of the porcine class pi glutathione S-transferase against urea. The presence of glutathione caused a shift in the equilibrium-unfolding curves towards lower urea concentrations and enhanced the first-order rate constant for unfolding suggesting a destabilisation of the pGSTPl-l structure against urea. The presence of either glutathione sulphonate or S-hexylglutathione, however, produced the opposite effect in that their binding to the G-site appeared to exert a stabilising effect against urea. The binding of these glutathione analogues also reduced significantly the degree of cooperativity of unfolding indicating a possible change in the protein's unfolding pathway.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg, 1996
Keywords: Biochemistry; Ligands (Biochemistry); Enzymes